2019
DOI: 10.2298/jas1903293t
|View full text |Cite
|
Sign up to set email alerts
|

The impact of enterprise size on the profitability of agricultural enterprises in the Republic of Serbia

Abstract: Sažetak: Veličina preduzeća je jedna od najbitnih determinanti profitabilnosti preduzeća. Pojedini domaći i brojni inostrani autori su pokušali da ukažu na uticaj koji veličina preduzeća ima na profitabilnost. Rezultati tih istraživanja su bili kontradiktorni, naime, neka istraživanja su pokazala da su veća preduzeća profitabilnija, neka da su manja preduzeća profitabilnija, a postoje i ona istraživanja koja su ukazala da veličina preduzeća nema uticaja na profitabilnost. Upravo ovi oprečni zaključci naveli su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…A statistically significant, positive contribution to profitability is observed with the variable of company size, while a negative contribution is noted in indebtedness, materiality, liquidity, and inflation. Similar research results were presented by Tomašević (2020), who concludes that liquidity, indebtedness, gross domestic product, and inflation have a negative and statistically significant contribution to the profitability of food companies, while only the size of the company makes a positive contribution to the profitability.…”
Section: Literature Reviewsupporting
confidence: 84%
See 1 more Smart Citation
“…A statistically significant, positive contribution to profitability is observed with the variable of company size, while a negative contribution is noted in indebtedness, materiality, liquidity, and inflation. Similar research results were presented by Tomašević (2020), who concludes that liquidity, indebtedness, gross domestic product, and inflation have a negative and statistically significant contribution to the profitability of food companies, while only the size of the company makes a positive contribution to the profitability.…”
Section: Literature Reviewsupporting
confidence: 84%
“…This is particularly important in the food industry, where challenges such as changing market demands, regulatory requirements, and the complexity of resource management can significantly affect financial performance. In defining the determinants of profitability, Tomašević (2020) explains that it is impossible to consider all the determinants of profitability and that the interpretation of such analysis results would be questionable due to complexity. Also, too small a number of determinants cannot be included because the formed model most likely ignores the effect of other determinants with greater influence, and the results of such research are inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the position of large agricultural companies in the Republic of Serbia does not significantly differ from the position of SMEs. For instance, Tomašević et al (2019) find that large agricultural companies report higher profitability than agricultural SMEs, but this difference is not statistically significant.…”
Section: Introductionmentioning
confidence: 90%
“…Jolović et al (2014) concluded that the financing of agriculture in Serbia is significantly below the importance of that sector and promote an increase of lending to agriculture. However, Tomašević et al (2014) analysed financial situation of agricultural companies in Serbia over a period of three years. Analysis of indebtedness showed that debts of agricultural enterprises is higher than 50% and they suggest limitation of further borrowing.…”
Section: Introductionmentioning
confidence: 99%